Freedom without foundations: Huxley, Arendt, and a pragmatist defense against ideology. - Yumbe, Patricia (Revista Estudios de Filosofía)
This paper offers a pragmatist defense of freedom in a post-realist world. Taking as its starting point the challenge posed to normative anti-realism—if there are no moral truths, what prevents politics from devolving into ideological domination?—it argues that freedom must be sustained not by metaphysical guarantees but by practices of critical thinking. To develop this claim, the paper reads Aldous Huxley’s Brave New World and Brave New World Revisited alongside Hannah Arendt’s reflections on ideology and thinking, situating both within the pragmatist tradition of William James, John Dewey, and Jane Addams. Huxley exposes the dangers of ideological conformity through pleasure and manipulation, while Arendt shows that freedom depends on the fragile space of appearance sustained by thought and dialogue. Drawing on Dewey’s democracy as inquiry, Addams’s ethics of community, and James’s pluralism, the paper argues that freedom is a practice of resisting closure and keeping the world open.